Development of Youth Communities in the University Ecosystem: Resources, Projects, and Risks - A. V. Kiryakova; N. A. Kargapoltseva; I. D. Belonovskaya; S. A. Duzhnikov (Moscow Polytechnic University, 2022)
The article explores the development of youth communities in the ecosystem of the Orenburg State University. The modern university is designed to create new conditions for the development of youth communities. The study of students' creative challenges demonstrates a wide range of aspirations and needs, their uncertainty and spontaneity. The answer to creative challenges is timely competent navigation and organizational and pedagogical support of young people for integration into socially positive communities. A regional university can become a center, space and mobilizer for the development of youth communities. Youth communities are dynamically changing, their reality goes beyond educational and scientific activities. In this regard, the traditional scientist-oriented model of the university is being transformed into an ecosystem model, which equally reveals the areas of training, development and education. Modern education at the empirical level masters the ecosystem approach. The article aims at revealing resources, projects, and risks of youth communities development in the conditions of the formation of a regional university ecosystem. The subject of study is the structure, axiological, organizational and procedural foundations of the university ecosystem. The resources, methods and risks of developing modern youth communities also represent the perspective of the study of the humanities. Ecosystem resources of the Orenburg State University are presented in many aspects: axiology and pedagogical technologies, projects of the Priority 2030 program, integration with the Orenburg University (Educational) District Association, international educational cooperation with universities in Kazakhstan. The article identifies external and internal risks specific to the development of youth communities in the logic of "potential applicants - university ecosystem - potential employers" based on the study of accelerator programs, streams, online surveys.